2007
DOI: 10.1016/j.marenvres.2006.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on scope for growth and accumulation of Cd, Co, Cu and Pb by the marine bivalve Mytilus edulis

Abstract: In many aquatic organisms including Mytilus edulis, the role of temperature on bioaccumulation of metals is still not clearly understood. In this study, uptake and accumulation of Cu, Co, Cd and Pb in mussels were investigated at different temperatures (6-26 degrees C). Results from exposure of isolated gills showed a positive relationship between temperature and metal uptake. But in whole organism experiments, only the accumulations of non-essential metals (Cd, Pb) showed a similar trend while the two essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(83 citation statements)
references
References 34 publications
5
74
1
3
Order By: Relevance
“…The water temperature and salinity at each of the respective sites varied greatly however salinity and temperature probes for these sites would need to be monitored long term in order to assess maximum and minimum values to be more accurate. A positive relationship between metal uptake and temperature has been reported meaning that different temperatures could affect SFG measurements specifically in relation to contaminants (Mubiana and Blust, 2007). In the present study, a positive correlation was observed between respiration and water temperature.…”
Section: Discussionsupporting
confidence: 69%
“…The water temperature and salinity at each of the respective sites varied greatly however salinity and temperature probes for these sites would need to be monitored long term in order to assess maximum and minimum values to be more accurate. A positive relationship between metal uptake and temperature has been reported meaning that different temperatures could affect SFG measurements specifically in relation to contaminants (Mubiana and Blust, 2007). In the present study, a positive correlation was observed between respiration and water temperature.…”
Section: Discussionsupporting
confidence: 69%
“…Previous research generally has shown that clams incorporate Pb into their shells in relation to ambient water concentrations (Babukutty & Chacko 1992, Pitts & Wallace 1994, Almeida et al 1998, Boisson et al 1998; however, these studies did not examine the relationship at different temperatures or salinities. More recently Mubiana & Blust (2007) showed that Pb uptake into soft tissue is positively correlated to temperature, but they did not examine the effects of temperature on Pb uptake into shell. It is difficult to discern the underlying causes of the significant relationship between temperature and juvenile shell D Pb that we found.…”
Section: Barium and Lead Uptakementioning
confidence: 99%
“…Previous research generally has shown that clams incorporate Pb into their shells in relation to ambient water concentrations (Babukutty and Chacko, 1992;Almeida et al, 1998;, however these studies do not examine the relationship at different temperatures or salinities. More recently Mubiana and Blust (2007) showed that Pb uptake into soft tissue is positively correlated to temperature, but they did not examine the effects of temperature on Pb uptake into shell. It is difficult to discern the underlying causes of the significant relationship between temperature and juvenile shell Dpb that we found.…”
Section: Barium and Lead Uptakementioning
confidence: 99%